Critical Analysis of Hadith Regarding Investment Ethics Standards: Examining Authenticity and Relevance - Kintabuwana, Kardita; Ali Masrur; Tajul Arifin (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2025)
The volatile global economy necessitates ethical investment frameworks, where Islamic finance offers a unique values-based model. However, a significant gap persists in the literature: the rigorous application of Hadith criticism to authenticate and contextualize the prophetic traditions underpinning Islamic investment ethics. This study addresses this by critically examining key hadith concerning Islamic ethical standards like riba, gharar, and maysir, and principles of justice. This research aims to demonstrate how critically authenticated hadith can be effectively applied in modern Islamic financial products and policies, fostering greater transparency and ethical integrity. Employing a qualitative library research approach with content and historical-critical analysis, we apply hadith criticism methodologies—including jarh wa ta'dil, sanad analysis, matn criticism, and ilal al-hadith—to selected texts from canonical collections. The findings of this study indicate that the majority of the key hadiths analyzed are classified as either sahih or at least hasan, thereby providing a strong and authoritative normative foundation for the formulation of Islamic investment ethical standards and enabling their practical application in the modern Islamic finance industry. The main contribution of this research lies in integrating the tradition of Hadith scholarship with the practice of Islamic economic ethics, a connection that has thus far been underexplored in academic literature. Ultimately, this study proposes a methodologically sound framework of Islamic investment ethics, bridging traditional Hadith studies with contemporary finance to promote a more resilient and ethical global financial system.